2020
DOI: 10.1371/journal.pgen.1009128
|View full text |Cite
|
Sign up to set email alerts
|

The Bric-à-Brac BTB/POZ transcription factors are necessary in niche cells for germline stem cells establishment and homeostasis through control of BMP/DPP signaling in the Drosophila melanogaster ovary

Abstract: Many studies have focused on the mechanisms of stem cell maintenance via their interaction with a particular niche or microenvironment in adult tissues, but how formation of a functional niche is initiated, including how stem cells within a niche are established, is less well understood. Adult Drosophila melanogaster ovary Germline Stem Cell (GSC) niches are comprised of somatic cells forming a stack called a Terminal Filament (TF) and associated Cap and Escort Cells (CCs and ECs, respectively), which are in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Drosophila ovary is a model system for understanding the stem cell niche, yet the genetic mechanisms underlying establishment of the niche remain largely unknown. To date, only three transcription factors, Bab, Lmx1a and En/Inv, have been identified as essential factors for the formation or proper stacking of TFs [ 18 , 25 , 26 ]. In this study, we characterized the function of Lola in regulation of ovary development in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Drosophila ovary is a model system for understanding the stem cell niche, yet the genetic mechanisms underlying establishment of the niche remain largely unknown. To date, only three transcription factors, Bab, Lmx1a and En/Inv, have been identified as essential factors for the formation or proper stacking of TFs [ 18 , 25 , 26 ]. In this study, we characterized the function of Lola in regulation of ovary development in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…By using two independent lola RNAi lines ( lola 12574 and lola 12052R-1 ) driven by somatic drivers c587-Gal4 and Tj-Gal4 , we showed that lola is required for the formation of TFs at the time when ovarian stem cell niche is established. It has been shown that Bab is involved in the formation of TFs [ 18 , 22 ]. Similar to Bab protein, Lola also contains the BTB domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these signaling pathways, a few genes, including twinstar (tsr), bric-à-brac (bab1/bab2), LIM homeobox transcription factor 1 alpha (Lmx1a) and longitudinals lacking (lola), have been reported to be involved in TFC formation [46][47][48][49][50]. Chen et al found that in tsr mutant ovaries, the TFC number decreased and all TFCs have a rounded appearance.…”
Section: Pathways That Regulate Tfc Formationmentioning
confidence: 99%